KOMUNIKASI ORGANISASI BERBASIS ELEKTRONIK - Akil, Muhammad Anshar (Jurnal Dakwah Tabligh, 2018)
Humans are organizational beings. Since entering the world, a person is always in the organization. Either the smallest organization such as family or Neighborhood Association (RT) until the greatest of organization is countries. Organization is a medium-to-life interdependence of goals. In order for the organization to run effectively it is necessary. Organizational communication can be either vertical or horizontal communication. In the current era of communication and information technology, every organization is required to use electronic technology. The electronic technology, both hardware, software, and networking, help organization can be more effective and efficient in achieving its goals. In addition, through electronic networks, the organization can serve the public without being limited by time and place, so that organizational goals can be more easily realized.